Molecular phylogeny, diagnostics, and diversity of plant-parasitic nematodes of the genus Hemicycliophora (Nematoda: Hemicycliophoridae) - Subbotin, Sergei A. (2014)
The genus Hemicycliophora (Nematoda: Hemicycliophoridae) contains 132 valid species of plant-parasitic nematodes, collectively known as ‘sheath nematodes’. Hemicycliophora spp. are characterized morphologically by a long stylet with rounded basal knobs and a cuticular sheath, present in juvenile and adult stages. Populations of 20 valid and 14 putative species of Hemicycliophora and Loofia from several countries were characterized morphologically using light (LM) and scanning electron microscopy (SEM) and molecularly using the D2-D3 segments of 28S rRNA and internal transcribed spacer (ITS) rRNA gene sequences. LM and SEM observations provided new details on the morphology of these species. PCR-restriction fragment length polymorphisms (PCR-RFLPs) of the D2-D3 of 28S rDNA were proposed for identification of the species. Phylogenetic relationships within populations of 36 species of the genus Hemicycliophora using 102 D2-D3 of 28S rDNA and 97 ITS rRNA gene sequences as inferred from Bayesian analysis are reconstructed and discussed. Ancestral state reconstructions of diagnostic characters (body and stylet length, number of body annuli, shape of vulval lip and tail), using maximum parsimony and Bayesian inference, revealed that none of the traits are individually reliable characters for classifying the studied sheath nematode. The Shimodaira–Hasegawa test rejected the validity of the genus Loofia. This is the most complete phylogenetic analysis of Hemicycliophora species conducted so far.